Development of Cooperative Learning Think-Talk-Write (TTW) Models Based on Batak Culture to Improve Students’ Mathematical Critical Thinking Ability - Ainin, Qurratu; Mulyono, Mulyono; Syahputra, Edi (Al-Jabar: Jurnal Pendidikan Matematika, 2020)
This study aimed to develop valid, practical, and effective Think-Talk-Write (TTW) learning tools based on Batak culture. Plomp's research design was used in this study. This development research product was a valid, practical, and effective TTW learning tools based on Batak culture, which can improve students' mathematical critical thinking ability. The results of the study are (1) TTW learning model based on Batak culture belonged to the valid category; (2) the practicality of the TTW learning tools based on Batak culture belonged to the high category; and (3) the effectiveness of the TTW learning tools based on Batak culture based on (a) classical student learning completeness was 88.89%; (b) the use of learning time criteria was in the high category; (c) the teacher's ability to manage learning criteria was in the high category, and (d) many students gave positive responses to the components and learning activities.